A multilocus variable number tandem repeat analysis assay provides high discrimination for genotypingLeptospira santarosaistrains. Issue 5 (May 2015) - Hamond, Camila; Pinna, Melissa; Medeiros, Marco Alberto; Bourhy, Pascale; Lilenbaum, Walter; Picardeau, Mathieu
Abstract : N/A: Considering the prevalence of Leptospira santarosai infections in the Americas and the scarce information about the species, we aimed to apply a multilocus variable number tandem repeat (VNTR) analysis (MLVA) for the molecular typing of L. santarosai isolates from various sources. Amplification of three VNTR loci selected from L. santarosai genome sequences resulted in a wide range of sizes for the amplified products amongst the 21 L. santarosai strains analysed. This suggested a variation in tandem repeat copy numbers in the VNTR loci. secY sequencing also showed a high nucleotide diversity, confirming the MLVA data. In conclusion, this novel MLVA provided a high level of discrimination between L. santarosai isolates, and this new typing tool could be used to investigate leptospirosis in regions where L. santarosai predominates.